Comparing the Pathology, Clinical, and Demographic Characteristics of Younger and Older‐Onset Multiple Sclerosis - Sarah Knowles (Annals of Neurology, 2024)
Objective: Older people with multiple sclerosis have a less active radiological and clinical presentation, but many still attain significant levels of disability; but what drives worsening disability in this group?Methods: We used data from the UK MS Register to characterise demographics and clinical features of late-onset multiple sclerosis (LOMS; symptom onset at ≥50 years), compared to adult-onset MS (AOMS; onset 18-49 years). We performed a pathology study of a separate MS cohort with a later onset (n=18, mean age of onset 54 years) versus AOMS (n=23, age of onset 30 years).Results: In the Register cohort there were 1608 (9.4%) with LOMS. When compared with AOMS, there was a lower proportion of females, a higher proportion of primary progressive MS, a higher level of disability at diagnosis (median MS impact scale 36.7 v 28.3, p<0.001), and a higher proportion of gait-related initial symptoms. People with LOMS were less likely to receive a high efficacy disease modifying treatment and attained substantial disability sooner.Controlling for age of death and sex, neuron density in the thalamus and pons decreased with onset-age, whilst actively demyelinating lesions and compartmentalised inflammation was greatest in AOMS. Only neuron density, and not demyelination or the extent of compartmentalised inflammation, correlated with disability outcomes in older-onset MS.Interpretation: The more progressive nature of older-onset MS is associated with significant neurodegeneration but infrequent inflammatory demyelination. These findings have implications for the assessment and treatment of MS in older people.